Indeks Eksentrisitas Zagreb Pertama dan Kedua Graf Koprima dari Grup Matriks Upper Unitriangular atas Ring Bilangan Bulat Modulo Prima - Abdillah, Muhammad Aris; Ismiarti, Dewi (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2022)
The coprime graph of a group G is a graph Γ_G with G is its set of vertices and any two distinct vertices are adjacent if and only if their order are relatively prime. Let p be a prime number, then G_p denotes the multiplicative group of 2×2 upper unitriangular matrices over ring of integers modulo p. The purposes of this research are to study the coprime graph Γ_(G_p ) and find the first and the second Zagreb eccentricity indices of Γ_(G_p ) for p≥3. The results of this research are as follows. First Zagreb eccentricity index of coprime graph Γ_(G_p )isE_1 (Γ_(G_p ))=4p-3. Second Zagreb eccentricity index of coprime graph Γ_(G_p )isE_2 (Γ_(G_p ))=2p-2.